The Abra del rock shelter, northwestern Argentina, a space ocuppied by hunter-gatherers that was hit by the large 4.2 ka Cerro Blanco eruption - Carbonelli, Juan Pablo; Fernandez Turiel, Jose Luis; Belotti López de Medina, Carlos Raúl (Elsevier Ltd, 2022)
Occupation sites have been rarely found during research on the prehistorical hunter-gatherer populations in the Andean intermontane valleys. Some reasons are the intense anthropization of the landscape and the scarce research efforts. Recent work opens new perspectives at the Abra del Toro rock shelter in the Yocavil valley (province of Catamarca, Argentina). Stratigraphy of rock shelter shows a 1 m thick volcanic ash deposit formed by wind transportation from primary ash-fall deposits. Geomorphological, sedimentological, textural, glass and mineral content, bulk chemical composition, and radiocarbon dating prove the tephra derived from the 4.2 ka BP eruption of the Cerro Blanco Volcanic Complex in the southern Puna. This is the world's largest documented volcanic eruption in the past five thousand years, and it covered the archeological site surroundings with an approximately 1-meter-thick ash-fall layer. Throughout the stratigraphic sequence of the Abra del Toro rock shelter, we can hypothesize that there were three main occupational moments: two hunter-gatherer moments, separated by the record of the large volcanic eruption, and a latern agro-pottery period. The evidence of the catastrophic volcanic event in the Abra del Toro rock shelter makes it possible to predict future impact on the contemporaneous communities.